2022
DOI: 10.1111/1462-2920.16106
|View full text |Cite
|
Sign up to set email alerts
|

A lipopolysaccharide‐dependent phage infects a pseudomonad phytopathogen and can evolve to evade phage resistance

Abstract: Bacterial pathogens are major causes of crop diseases, leading to significant production losses. For instance, kiwifruit canker, caused by the phytopathogen Pseudomonas syringae pv. actinidiae (Psa), has posed a global challenge to kiwifruit production. Treatment with copper and antibiotics, whilst initially effective, is leading to the rise of bacterial resistance, requiring new biocontrol approaches. Previously, we isolated a group of closely related Psa phages with biocontrol potential, which represent envi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 98 publications
(140 reference statements)
0
9
0
Order By: Relevance
“…It also remains unknown what correlated phenotypic changes, in the context of behaviors like biofilm formation or in responses to LPS interacting molecules like cationic antimicrobials [50], might occur across P. syringae strains with fundamentally different LPS conformations. It is also highly likely that phage attachment and infection also greatly contributes to, and may indeed itself drive, modification of the LPS under natural conditions [40,51]. Our results highlight the potential for tailocins, or other LPS targeting bacteriocins [52], to be used as tools for uncovering and exploring genetic diversity in pathways and genes that underlie LPS production in these and other strains.…”
Section: Glycosyl-transferasesmentioning
confidence: 74%
See 1 more Smart Citation
“…It also remains unknown what correlated phenotypic changes, in the context of behaviors like biofilm formation or in responses to LPS interacting molecules like cationic antimicrobials [50], might occur across P. syringae strains with fundamentally different LPS conformations. It is also highly likely that phage attachment and infection also greatly contributes to, and may indeed itself drive, modification of the LPS under natural conditions [40,51]. Our results highlight the potential for tailocins, or other LPS targeting bacteriocins [52], to be used as tools for uncovering and exploring genetic diversity in pathways and genes that underlie LPS production in these and other strains.…”
Section: Glycosyl-transferasesmentioning
confidence: 74%
“…For class A genomes, the presence of an apparent orthologue of wzm as well an ATPase are significantly correlated with tailocin sensitivity. In P. aeruginosa, rhamnose precursors of the CPA are transported from the cytoplasm of the cell by an ABC transporter (wzt/wzm), with energy provided by an ATPase, and with a fourth glycosyltransferase gene present in the operon to attach these sugars to the growing chain [19,40]. This particular operon in P. syringae is the same as highlighted by Jayaraman et al for its patterns of recombination and it is likely that this operon in tailocin sensitivity class A strains is carrying out the same activities as the wzt/wzm ABC transporter in P. aeruginosa.…”
Section: Permease)mentioning
confidence: 99%
“…In addition, it is important to note that many NAD-jumbo phages encode NAD-dependent enzyme genes, such as UDP-glucose 6-dehydrogenase (UGDH), UDP-glucose 4-epimerase (galE), and dTDP-glucose 4,6-dehydratase (rfbB), involved in lipopolysaccharide (LPS) biosynthesis (Figure 3, Table S9). Bacteria LPS is a rich and diverse cell wall polysaccharide, which was adopted by phages as receptor for infection [30, 31]. Phage-encoded synthesis of LPS may be able to change the modification of cell wall to prevent the infection of competing phages [32, 33].…”
Section: Resultsmentioning
confidence: 99%
“…This hypothesis is further corroborated by our global comparative transcriptomics analysis demonstrating the downregulation of LPS assembly associated genes following exposure to ΦBp-AMP1. Indeed, the LPS is a well-known receptor for many different bacteriophages and mutations of LPS confer resistance to phage in a variety of bacteria [50][51][52][53] , whereas capsular polysaccharides have recently been shown to serve as primary receptors of E. coli phage 54,55 . Moreover, it has been reported that B. pseudomallei displays various colony morphotypes based on O-antigen variations 56 .…”
Section: Emergence Of Resistance To Phagementioning
confidence: 99%